Competência em informação, gestão da informação e do conhecimento: um estudo com gestores da Biblioteca Central da Universidade Federal da Paraíba - Anjos, Clebson Leandro Beserra dos (2017)
There is a problem in the contemporary society referred to the excess of information that is produced and disseminated through information technology and communication, especially, the Internet. In this context, the library managers, who are information professionals, have to improve themselves through competence practices in information, in order to search, to access and to use the information in a efficient way, managing its growing flux to create knowledge in sphere of the organization. In this scenario, the objective is verify the manner the competence in information of the managers of the Central Library of Federal University of Paraíba can contribute to the development of the information management practices and knowledge management. For that, it was realized a exploratory and descriptive study, through data analysis and an observation in order to identify the practices of competence in information, information management and knowledge management of unit managers. The results revealed that most managers have the competence to identify the need for information and knowledge and to acquire, disseminate and use them. However, managers and employees need more motivation and encouragement to share knowledge and to expand their use through new information services and products in the unit. It is concluded that the information competence can effectively contribute to the development and improvement of information management and knowledge management processes in the researched unit.